The Development of a Model for Health Resort Businesses to Take Care of Health and Support the Aging Society by Creating High-Value Services for Small Hotel Businesses - Mukda, Wipada; Kuensman, Wanphen; Kansarnsanti, Varistha (Asia Social Issues, 2025)
This research aimed to: 1) study the process of developing a health resort business model; 2) create a health resort business model; and 3) propose guidelines for developing a health resort business model that supports the aging society by providing high-value services for small hotel businesses. A mixed-methods approach was used, combining quantitative and qualitative research. For the quantitative aspect, questionnaires were administered to 400 older people, and the data were analyzed using frequency, percentage, mean, and standard deviation. In contrast, the qualitative aspect involved in-depth interviews with representatives from small hotels, hospital, Sub-district Administrative Organization, and public health officials at Sub-district Health Promoting Hospital, involving 100 individuals. The qualitative data were subjected to content analysis. The findings revealed that: the elderly engaged in health promotion and care activities such as disease prevention, rehabilitation, and medical treatment. They required health services in terms of physical, economic, social, and mental/emotional aspects. Health resorts were found to effectively care for the elderly by providing a supportive environment, emergency preparedness, expert care, and appropriate facilities. Guidelines for developing health resort prototypes emphasize reliability, proper licensing, comprehensive facilities, a good environment, food and activities, safety standards, and alternative medicine services to address health issues.